The Effectiveness of Scarification Technique to Break Dormancy Kenaf Seed (Hibiscus cannabinus L.) - Taufiq Hidayat Rahman Side; Retno Mastuti; Athifah Rosi Widiani (Jurnal Penelitian Tanaman Industri, 2021)
The kenaf seeds have a hard seed surface structure, seed trichomes, and attached hilum cap tightly that can inhibit the kenaf seed germination process and become one of the causes of physical dormancy. Physical dormancy can be broken by scarification techniques. There are three scarification techniques, namely mechanical, physical, and chemical scarification. This study aimed to determine which scarification techniques were effective against the breaking of kenaf seed dormancy. The research was carried out at the Seed Laboratory of the Indonesian Sweetener and Fiber Crops Research Institute in January-May 2019. The research method used a randomized block design consisting of seven scarification treatments with four replications. The treatment consists of mechanical treatment, water soaking treatment at 70ºC for 3 hours, water soaking treatment at 80ºC for 3 hours, water soaking treatment at 90ºC for 3 hours, H2SO4 98% soaking for 5 minutes, H2SO4 98% soaking for 10 minutes and H2SO4 98% soaking for 15 minutes. The results showed that the scarification technique had a significant effect on increasing the viability of kenaf seeds. Scarification treatment with H2SO4 98% soaking for 5 minutes effectively broke the dormancy of kenaf seed. It could improve the germination of kenaf seeds up to 6%, reduce the number of seed trichomes, and effectively exfoliate the hilum cap. The study suggest that soaking the kenaf seeds in H2SO4 98% for 10 minutes could be adopted to break the seed dormancy to improve the germination.Keywords: dormancy, Hibiscus cannabinus, hilum cap, scarification, seed trichome ABSTRAKEFEKTIVITAS TEKNIK SKARIFIKASI UNTUK MEMATAHKAN DORMANSI BENIH KENAF (Hibiscus cannabinus L.)Benih kenaf memiliki struktur permukaan yang keras, trikoma, dan penutup hilum yang menempel kuat. Hal ini dapat menghambat proses perkecambahan benih kenaf dan menjadi salah satu penyebab dormansi fisik. Dormansi fisik dapat dipatahkan dengan teknik skarifikasi. Terdapat tiga teknik skarifikasi, yaitu skarifikasi mekanik, fisik, dan kimia. Tujuan penelitian ini yaitu untuk mengetahui teknik skarifikasi yang efektif terhadap pematahan dormansi benih kenaf. Penelitian dilaksanakan di Laboratorium Benih Balai Penelitian Tanaman Pemanis dan Serat pada bulan Januari-Mei 2019. Metode penelitian menggunakan rancangan acak kelompok yang terdiri atas tujuh perlakuan skarifikasi benih kenaf dengan empat ulangan. Perlakuan terdiri dari perlakuan mekanik, perendaman air suhu 70ºC selama 3 jam, perendaman air suhu 80ºC selama 3 jam, perendaman air suhu 90ºC selama 3 jam, perendaman H2SO4 98%  selama 5 menit, perendaman H2SO4 98% selama 10 menit dan perendaman H2SO4 98% selama 15 menit. Banyaknya benih tiap perlakuan adalah 400 biji. Hasil penelitian menunjukkan bahwa teknik skarifikasi berpengaruh nyata terhadap pematahan dormansi benih kenaf. Perlakuan skarifikasi dengan perendaman H2SO4 98% selama 5 menit efektif mematahkan dormansi benih kenaf dan meningkatkan daya berkecambah benih kenaf hingga 6% dan mampu mereduksi jumlah trikoma benih dan efektif dalam pengelupasan hilum cap. Metode pematahan dormansi benih kenaf perlu dikembangkan untuk meningkatkan efektifitasnya.Kata kunci : dormansi, Hibiscus cannabinus, hilum cap, skarifikasi, trikoma benih